THE FAUNA OF ARGASIDAE AND THE ROLE OF ORNITHODOROS IN RELAPSING FEVER IN SOME VILLAGES OF THE CENTRAL PROVINCE OF IRAN - M. Salimi; M. Asmar; N. Piazak (Tehran University of Medical Sciences, 1996)
In order to study the distribution of Argasidae family ticks and the role of O.tholozani in transmitting the relapsing fever agent in rural areas of central province, an investigation was carried out from June to November 1992. In this study, 3371 specimens from 70 villages were collected by simple sampling method technique and subsequently were identified in laboratory. The results showed that frequencies of O.lahurensis, O.lahurensis, O.canesterini and Argas presicus were 60.90%, 4.21%, 11.81% and 23.08% respectively. O.tholozani specimens collected from Vafs zone appeared to be infected with Borrelia persica and thus capable of transmitting the disease. This finding can be regarded as an alarm for adopting proper measures to control incriminated vector.